Ecological Design . - Roth, Manuela (Kempen TeNeues, 2008)
With a growing emphasis on green living, the design world is becoming more ecological. These groundbreaking designs appeal to the eye, the mind—and the planet. And there’s a dash of whimsy as well! It includes chapters on furniture, lighting, housewares, children’s goods, industrial design, office design, electronics, fashion and accessories, and transport. This latest volume in our Styleguide series showcases the successful marriage of style and sustainability in product design
Keywords: Design - History - 21th century - Catalogs